Evaluation of neonicotinoid insecticides for oestrogenic, thyroidogenic and adipogenic activity reveals imidacloprid causes lipid accumulation. Issue 12 (27th June 2018) - Mesnage, Robin; Biserni, Martina; Genkova, Dilyana; Wesolowski, Ludovic; Antoniou, Michael N.
Abstract: Few studies have investigated non‐target effects of neonicotinoid insecticides on mammalian physiology. This is largely due to the widespread perception that their weak affinity for nicotinic acetylcholine receptor subtypes in vertebrates makes mammalian exposures unlikely to pose health risks. To the best of our knowledge, we describe the first investigation evaluating the interaction of seven principal neonicotinoid insecticides (thiamethoxam, imidacloprid, clothianidin, flupyradifurone, dinotefuran, nitenpyram, thiacloprid) with oestrogen and thyroid hormone receptors, as well as their adipogenic effects, in mammalian cell culture assay systems. An E‐Screen with MCF‐7 and T‐Screen with GH3 cells respectively showed a lack of oestrogen and thyroid hormone receptor agonist effects for any of the neonicotinoids tested. Adipogenicity was assessed by the ability to stimulate lipid accumulation in adipocyte differentiated 3T3‐L1 cells, with only imidacloprid scoring positive in this assay causing triglyceride accumulation from a concentration of 50 mg l −1 . Data mining of ToxCast high‐throughput screening assays revealed that this adipogenic effect of imidacloprid is probably mediated via the pregnane X receptor. Abstract : The oestrogenic, thyroidogenic and adipogenic potential of seven neonicotinoid insecticides (thiamethoxam, imidacloprid, clothianidin, flupyradifurone, dinotefuran, nitenpyram, thiacloprid) were studied in mammalian cell lines. None of the neonicotinoids tested displayed any oestrogen and thyroid hormone agonist properties in receptor‐mediated cell proliferation assays. Only imidacloprid caused triglyceride accumulation in the 3T3‐L1 adipogenicity cell assay. Data mining of ToxCast high‐throughput screening assays revealed that this adipogenic effect of imidacloprid is probably mediated via the pregnane X receptor.